2003
DOI: 10.1055/s-2003-36407
|View full text |Cite
|
Sign up to set email alerts
|

Open-Access Endoscopy: Are Age-Based Guidelines Justified? An Audit of Experience of 1000 Open-Access Endoscopies at a District General Hospital

Abstract: If current guidelines are applied, all cases of malignancy may be picked up, but identification of patients with curable disease is poor. Use of the guidelines did not select patients with other upper gastrointestinal disease, although many patients were receiving acid-suppression therapy at the time of their endoscopy. Implementation of test-and-treat strategies would result in a significant reduction in the workload of open-access endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…16 Diagnostic performance for failure of antacid medication from three studies [22][23][24] showed a low association with oesophagogastric cancer (Table 2).…”
Section: Other Symptomsmentioning
confidence: 99%
“…16 Diagnostic performance for failure of antacid medication from three studies [22][23][24] showed a low association with oesophagogastric cancer (Table 2).…”
Section: Other Symptomsmentioning
confidence: 99%
“…Due to a selection bias, the paper by Boldys et al [13] clearly overemphasizes the issue of young and asymptomatic patients with gastric cancer. The observational study by Boulton et al [18] seems to come closer to the real situation, as one out of 17 patients with gastric cancer (and with alarm symptoms) was less than 45 years old. In 2088 consecutive patients studied prospectively, we found 26 gastroesophageal cancers, two of which (7.6 %) indeed occurred in patients younger than 45 [12].…”
mentioning
confidence: 89%
“…The paper by Boulton-Jones et al [18] reviews the appropriateness and diagnostic yield of 1000 consecutive open-access referrals for upper gastrointestinal endoscopy in a UK district hospital. One-third of the procedures were found to be inappropriate according to the guidelines of the British Society of Gastroenterology (BSG).…”
mentioning
confidence: 99%
See 2 more Smart Citations